46.1: Invited Paper: Ink‐jet Printed 17‐inch AMOLED Display with Amorphous IGZO TFTs Backplane. Issue 1 (1st July 2013) - Liu, Ze; Wang, Gang; Xie, Hongjun; Wu, Zhongyuan; Li, Yanzhao; Jiang, Chunsheng; Yin, Jingwen; Yang, Fei; Song, Danna; Yuan, Guangcai; Sun, Li; Hou, Wenjun; et al.
Abstract: A 17‐inch full‐color active matrix organic light‐emitting diode (AMOLED) display has been developed, which combine with amorphous indium‐gallium‐zinc oxide (IGZO) thin film transistors and ink‐jet printing technology. It was also proved that ink‐jet printing technology can be used for large size AMOLED panel fabrication on IGZO thin film transistor backplane.